Estimating belowground carbon stocks in peatlands of the Ecuadorian páramo using ground‐penetrating radar (GPR). Issue 2 (18th February 2017) - Comas, Xavier; Terry, Neil; Hribljan, John A.; Lilleskov, Erik A.; Suarez, Esteban; Chimner, Rodney A.; Kolka, Randy K.
Abstract: The páramo ecoregion of Ecuador contains extensive peatlands that are known to contain carbon (C) dense soils capable of long‐term C storage. Although high‐altitude mountain peatlands are typically small when compared to low‐altitude peatlands, they are abundant across the Andean landscape and are likely a key component in regional C cycling. Since efforts to quantify peatland distribution and C stocks across the tropical Andes have been limited due to the difficulty in sampling remote areas with very deep peat, there is a large knowledge gap in our quantification of the current C pools in the Andean mountains, which limits our ability to predict and monitor change from high rates of land use and climate change. In this paper we tested if ground‐penetrating radar (GPR), combined with manual coring and C analysis, could be used for estimating C stocks in peatlands of the Ecuadorian páramo. Our results indicated that GPR was successful in quantifying peat depths and carbon stocks. Detection of volcanic horizons like tephra layers allowed further refinement of variability of C stocks within the peat column, while providing information on the lateral extent of tephras at high (centimeter‐scale) resolution that may prove very useful for the correlation of time‐stratigraphic markers between sediments in alpine peatlands. In conclusion, this paper provides a methodological basis for quantifying C stocks in high‐altitude peatlands and to infer changes in the physical properties of soils that could be used as proxies for C content or paleoclimate reconstructions. Key Points: Ground‐penetrating radar was tested to quantify peat depths and refine C stocks in the Ecuadorian páramo Imaging of tephras and changes in the reflection record show potential for time‐stratigraphic correlations in alpine peatlands A linear relationship was developed for estimating total C stock based on total peat volume in the Ecuadorian páramo